PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI WALI NAGARI KECAMATAN LINGGO SARIBAGANTI - Nia Rahmadani; Reni Respita; Detman (Ekasakti Educational Scientific Journal, 2023)
The purpose of this study is to find out the influence of work motivation and job satisfaction on the performance of Wali Nagari employees of Linggo Saribaganti Subdistrict. This type of research is quantitative. The population of this study is an employee of Wali Nagari Linggo Saribaganti Subdistrict which amounted to 44 people taken in total sampling. Data is processed using multiple linear regression using questionnaires and hypotheses using the T test and Test F. The results showed that there is an influence between work motivation (X1) on employee performance and there is an influence between job satisfaction (X2) on employee performance in Wali Nagari Linggo Saribaganti Subdistrict. For Employees and Leaders in Wali Nagari District Linggo Sari Baganti must further improve its performance and motivate themselves more eager to work.